2007
DOI: 10.1118/1.2818729
|View full text |Cite
|
Sign up to set email alerts
|

Correction factors for low perturbation in vivo diodes used in the determination of entrance doses in high energy photon beams

Abstract: It is expected that it will be very difficult to achieve accurate in vivo dosimetry using the EDD2 diode. The EDD5 diode may represent a reasonable compromise between EDD2 and the full buildup EDP15. The EDD5 dose perturbation is small and the correction factors are not as large as for EDD2, so accurate in vivo dosimetry may be possible as long as the obliquity is below 45 degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Accordingly, care should be taken when using the EDD5 at energies around 9 MV or higher. The results of the present study are in general agreement with a previous report which concluded that the EDD5 may be applied as a low‐perturbation diode at high energies (particularly for the lower megavoltage beam energies) and for angles of obliquity below 45° (24) . Our results suggest against the use of this diode in axial angles beyond ±50° and exceeding the range 0° to +50° tilt angle at 9 MV, because a small error in setup for such angles may cause large errors in the diode readings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, care should be taken when using the EDD5 at energies around 9 MV or higher. The results of the present study are in general agreement with a previous report which concluded that the EDD5 may be applied as a low‐perturbation diode at high energies (particularly for the lower megavoltage beam energies) and for angles of obliquity below 45° (24) . Our results suggest against the use of this diode in axial angles beyond ±50° and exceeding the range 0° to +50° tilt angle at 9 MV, because a small error in setup for such angles may cause large errors in the diode readings.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, a significant perturbation of the target dose may occur if it is used on most or all of the treatment fractions. Given the importance of performing in vivo dosimetry in most or all of complex treatment fractions, using thin buildup (low‐perturbation) diodes instead is gathering interest (24) . However, such diodes are strictly unsuitable for dosimetry of high‐energy megavoltage photons.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Diodes are also designed to measure surface dose and dose from electron fields. 8,[10][11][12][13][14][15][16][17][18] This work is a study of diodes that are semiconductor detectors designed to measure surface dose. The surface-dose characteristic is accomplished with packaging that has an areal density of less than 0.1 g / cm 2 on the entrance side of the diode.…”
Section: Introductionmentioning
confidence: 99%
“…19 The average percentage of CF angle effect 0?6% was found to have an relatively enhanced effect on cumulative diode reading. SSD correction factor, block correction factor have relatively reduced effect on diode response by 0?3%, 0?1%.…”
Section: Discussionmentioning
confidence: 87%
“…Geometric parameters, e.g. [16][17][18][19][20] If build up cap of diode is not thick enough then an overestimation of dose at short SSD can be observed because of the electronic contamination seen by diode not IC at maximum depth dose.…”
Section: Introductionmentioning
confidence: 99%